La primera gran huelga de los constructores de calzado de Barcelona en 1903 - Joël Delhom (Cahiers de Civilisation Espagnole Contemporaine, 2015)
The daily analysis of the Barcelona shoemakers’ momentous strike in June and July 1903, based on reports from middle-class and labour newspapers, highlights on the one hand the tactical divergences between activists with differing ideological orientations and on the other hand the divisions inside the sociedad de resistencia (union) that launched the strike, divisions which are related to the evolution of the shoe industry. The employers’ and civil authorities’ attitude is also mentioned.